A comparison of the physical activity levels of 3-to-6-year-old children with autism spectrum disorder and children with typical development - Wang, Jing; Yao, Jiaxin; He, Yingli (Frontiers in Psychology, 2024)
Background: Physical activity during early development is closely related to health. Differences in physical activity between young children with autism spectrum disorder and those with typical development are unclear. The purpose of this study was to compare the physical activity levels in children with autism spectrum disorder and typically developing children from the same area, including their sedentary physical activity, light physical activity, moderate-to-vigorous physical activity, and number of days in which the moderate-to-vigorous physical activity guideline recommendation of 60 minutes per day was met.Methods: A total of 77 participants aged 3-6 years were included: 41 children with autism spectrum disorder (mean age=61.41 ±10.69 months) and 36 children with typical development (mean age=60.36 ±10.16 months). The physical activity of the children was measured using an ActiGraph GT3x accelerometer.Results: There were no significant differences in daily sedentary physical activity (439.70±54.98 v. 450.42±53.67) or moderate-to-vigorous physical activity (46.62±18.93 v. 47.47±18.26) between the two groups. The average daily moderate-to-vigorous physical activity of the two groups did not reach 60 minutes, and they had similar proportions of participants who reached 60 minutes a given number of times (24.4% v. 25%). Daily light physical activity was significantly higher in the autism spectrum disorder group (263.96±43.17 v. 242.32±37.91, p<0.05). The moderate-to-vigorous physical activity of both groups was similar and lower than the recommended minimum physical activity.Targeted interventions should be considered in early intervention programs for children with autism spectrum disorder to increase their moderate-to-vigorous physical activity.